Unveiling the Power of Exponential Functions: Applications in Our Daily Lives - Jha, Sagar; Sahani, Suresh Kumar; Sahani, Kameshwar (ARZUSIN, 2024)
In this research paper, we have obtained some new applications of exponential and logarithmic functions. This report deals all the validity of previous works. This work is motivated by the work of [1-12].